2016
DOI: 10.1021/acs.est.6b01919
|View full text |Cite
|
Sign up to set email alerts
|

Using the Novel Method of Nonthermal Plasma To Add Cl Active Sites on Activated Carbon for Removal of Mercury from Flue Gas

Abstract: A new method using nonthermal plasma to add Cl active sites on activated carbon was proposed to improve the efficiency of activated carbon (AC) for removal of mercury from flue gas. The experiments were conducted via a lab-scale dielectric barrier discharge nonthermal plasma system and a vertical adsorption reactor. The results showed that the nonthermal plasma treatment with a small amount of Cl successfully added Cl active sites on AC and greatly increased the mercury removal efficiency of AC by chemisorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…However, Hg 0 is extremely hard to be captured as a result of its extremely low water solubility and high volatility at room temperature . To control Hg 0 pollution, various Hg 0 purification technologies, consisting of catalytic oxidation, adsorption removal, chemical oxidation, etc., have been developed. Based on different oxidants and oxidation principles, Hg 0 chemical oxidation technologies can be further divided between conventional oxidation and free radical advanced oxidation …”
Section: Introductionmentioning
confidence: 99%
“…However, Hg 0 is extremely hard to be captured as a result of its extremely low water solubility and high volatility at room temperature . To control Hg 0 pollution, various Hg 0 purification technologies, consisting of catalytic oxidation, adsorption removal, chemical oxidation, etc., have been developed. Based on different oxidants and oxidation principles, Hg 0 chemical oxidation technologies can be further divided between conventional oxidation and free radical advanced oxidation …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, due to the element's (wide) exposition, to avoid adverse harmful effects to the respiratory, nervous and immune systems, it is crucial to decrease atmospheric mercury emissions. Conducted research confirms Energies 2021, 14, 2174 2 of 15 the severe influence on the environment and warrants worldwide actions for the reduction of emissions [6][7][8].…”
Section: Introductionmentioning
confidence: 64%
“…The stand for measuring mercury sorption from flue gases generated by the combustion of solid fuels is shown in Figure 1. The bench-scale measurement setup consists of tube furnace (3) along with temperature and gas flow regulation with quartz tube (4) as the combustion chamber, gas source (1) and sorbent holder (8). The utilized equipment allows for controllable gas heating at specified points (9).…”
Section: Mercury Adsorption Systemmentioning
confidence: 99%
“…The calculation results reveal that a N group has a neglectable effect on the Hg adsorption on porous carbon. 23 , 38 The Hg removal using carbon was investigated experimentally. They increased the nitrogen groups on the carbon surface by applying nonthermal plasma treatment under pure N 2 and found that the nitrogen group had no obvious effect on the Hg removal ability of carbon.…”
Section: Resultsmentioning
confidence: 99%